ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR PADA BURSA EFEK INDONESIA. - Eka Putri Anggraeni, 16.05.62.0002; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This research aims to test the influence of the Debt to Equity Ratio (DER), Return On Equity (ROE), Deviden Payment Ratio (DPR), Company Size (Size), and the Liquidity of the company value. The population in this research is included in the company Index LQ 45 on the Indonesia Stock Exchange (IDX) period in 2014-2016.The research sample was obtained by purposive sampling method. The type of data used in this research is secondary data.The research data were analyzed by using multiple linear regression test. The research results showed that the Return On Equity (ROE)has a significant positive effect and Company Size (Size) has a significant negative effect. While Dividend Payment Ratio (DPR) and Liquidity has a significant negative effect as well as the Debt to Equity Ratio (DER) has a positive effect not significant. Keywords : Debt to Equity Ratio (DER), Return On Equity (ROE), Deviden Payment Ratio (DPR), Company Size (Size), and Liquidity